UJI EFEKTIVITAS MEDIA DMEM BEBAS SERUM DENGAN PENAMBAHAN MADU Tetragonula sp DAN ROYAL JELLY Apis mellifera TERHADAP PROLIFERASI SEL FIBROBLAS KULIT PREPUTIUM - Qara Syifa Fachrani, (2020)
Fetal Bovine Serum (FBS) is widely used in research, for example stem cell engineering by protein transduction of fibroblast cells. An optimal culture medium is needed to increase protein transduction. To reduce protease, FBS is substituted with honey and royal jelly. This study aimed to determine the effectivity of serum-free DMEM medium with Tetragonula sp honey and royal jelly Apis mellifera on proliferation of fibroblasts preputium cells. The research design used true experimental methods. Samples taken from healthy people. Fibroblast cells were cultured with various concentrations of honey and royal jelly (0.1%, 1%, 5%), then measured with MTT test. Fibroblast cells cultured in Tetragonula sp honey and royal jelly Apis mallifera 0.1% medium had a significant difference, with proliferation higher than 1% (p=0,000) and 5% (p=0,000), but did not exceed proliferation in FBS medium. The addition of other components was needed to optimize proliferation in honey and royal jelly medium. The composition of honey and royal jelly, especially sugar, can inhibit fibroblast cells growth. This was indicated by decreased proliferation on 5% concentration. Isolation of active ingredients of proliferation in honey and royal jelly can be used as an alternative development of effective and safe substitute for FBS.